Defining law: the concept of force and its legitimacy (Società e diritti, 2019)
AbstractThe relation between force and law is very complicated one. However, if we want to understandwhat a rule is, what it can do, and how it does, we have to recognize the relevance of the coercivedimension; this is not a necessary character of every rule, but remains the most typical reasonthat explains why people accord their behaviors to the prescriptions of the rules. Dealing withforce, in any case, is not an easy matter: the semantic field to which the term force belongs isvery huge and with it we can cover a lot of different situations. For that reason, when we puttogether law and force, we immediately need to find a third element through which thisrelationship could be regulated. The force of law leads us to recognize that the acts of force wecan accept are the ones that have been defined by the legitimate principle. The coercivedimension is comprehensible just for its legitimacy, and that implies an idea of justice.The Author would like to stress her lecture of Schauer’s reflection on the force of law, is thataccording to the position that recognise of a force in the very core of law, we are immediatelyobliged to give to this force a plan in which it can assume a legal meaning, and that is to say,the uncertain ground of the metaphysical, transcendental idea of justice.Key words: Legal positivism, Justice, coercionRiassuntoLa relazione tra forza e diritto è molto complessa. Tuttavia, se vogliamo capire che cosa sia unanorma giuridica, che cosa possa fare, e come lo faccia, dobbiamo riconoscere l'importanza delladimensione coercitiva; questo non è un carattere necessario di ogni norma, ma resta la ragionepiù tipica che spiega perché le persone accordano i loro comportamenti alle prescrizioni deldiritto. Maneggiare il concetto di “forza”, in ogni caso, non è cosa semplice: il campo semanticodel termine ‘forza’ è molto grande e si riferisce ad un ampio numero di situazioni diverse. Perquesto motivo, quando accomuniamo la “legge” e la “forza”, abbiamo immediatamente bisognodi trovare un terzo elemento attraverso il quale questo rapporto possa essere regolamentato.La dimensione coercitiva è comprensibile solo alla luce del concetto di legittimità e implicaun'idea di giustizia. La forza della Legge ci porta a riconoscere che gli atti di forza che possiamoaccettare sono solo quelli che siano coperti dal principio di legittimità. L’autrice tiene asottolineare che la sua interpretazione della saggio di Schauer sulla “forza di legge”, è nel sensoche qualora si attribuisca la forza al nucleo centrale del concetto stesso di Diritto, saremmoimmediatamente obbligati a collocare questa forza su un piano in cui si può assumere unsignificato giuridico, vale a dire il terreno incerto dell’idea metafisica e trascendentale dellagiustizia.Parole chiave: positivismo giuridico, giustizia, coercizione